Immobilization of alpha-amylase onto poly(glycidyl methacrylate) grafted electrospun fibers by ATRP - OKTAY, BURCU; KAYAMAN APOHAN, NİLHAN; DEMİR, SERAP (ELSEVIER, 2015)
In this study, novel alpha-amylase immobilized poly(vinyl alcohol) (PVA) nanofibers were prepared. The PVA nanofiber surfaces were functionalized with 2-bromoisobutyryl bromide (BiBBr) and followed by surface initiated atom transfer radical polymerization (SI-ATRP) of glycidyl methacrylate (GMA). The morphology of the poly(glycidyl methacrylate) (PGMA) grafted PVA nanofibers was characterized by scanning electron microscopy (SEM). Also PGMA brushes were confirmed by X-ray photo electron microscopy (XPS). alpha-Amylase was immobilized in a one step process onto the PGMA grafted PVA nanofiber. The characteristic properties of the immobilized and free enzymes were examined. The thermal stability of the enzyme was improved and showed maximum activity at 37 degrees C by immobilization, pH values of the maximum activity of the free and immobilized enzymes were also found at 6.0 and 6.5, respectively. Free enzyme lost its activity completely within 15 days. The immobilized enzyme lost only 23.8% of its activity within 30 days. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Surface initiated atom transfer radical polymerization; Enzyme immobilization; Electrospun nanofiber; Reactive electrospinning; Polymer brushes; TRANSFER RADICAL POLYMERIZATION; COVALENT IMMOBILIZATION; GLYCIDYL METHACRYLATE; DINITROSALICYLIC ACID; ENZYME IMMOBILIZATION; POLY(VINYL ALCOHOL); EPOXY SUPPORTS; NANOFIBERS; OPTIMIZATION; BRUSHES